Viscoelastic damper connected to adjacent structures involving seismic isolation - Matsagar, Vasant Annasaheb; Jangid, Radhey Shyam (Journal of Civil Engineering and Management, 2005)
The seismic response of multi‐storied base‐isolated structure to various types of isolation systems connected using viscoelastic dampers to the adjacent dissimilar base‐isolated or fixed‐base structure is investigated. The multi‐storied structures are modelled as a shear type structures with lateral degree‐of‐freedom at each floor, which are connected at different floor levels by viscoelastic dampers. The performance of this combination is studied by deriving the governing equations of motion and solving it in the incremental form using Newmark’s step‐by‐step method of integration. The variation of top floor absolute acceleration of both the buildings and bearing displacement under different real earthquake ground motions is computed to study the behaviour and effectiveness of resulting connected system. It is concluded that connecting the two adjacent base‐isolated buildings with the viscoelastic dampers is useful in controlling large bearing displacements in the base‐isolated structures thereby eliminating the isolator damages arising due to instability at these large displacements or pounding with adjacent ground structures during earthquakes. The viscoelastic damper connection between adjacent structures is found to be most effective when the adjacent base‐isolated and fixed‐base buildings are connected. Such scheme is hence useful in upgrading the seismic performance of existing fixed‐base structures adjacent to a base‐isolated structure. Seisminei izoliacijai skirtas su gretimu statiniu sujungtas klampiai tamprus slopintuvas Santrauka. Tyrinėjamas daugiaaukščiu statiniu su įvairiomis izoliavimo sistemomis ir klampiai tampriais slopintuvais, sujungtais su kitais analogiškais statiniais, seisminis atsakas. Daugiaaukščiai pastatai modeliuoti šlyties tipo konstrukcijomis su skersiniais laisvės laipsniais kiekvienam aukštui. Aukštai sujungti skirtinguose lygiuose klampiai tampriais slopintuvais. Tokios sistemos laikysena tyrinėta sudarant pagrindines judėjimo lygtis ir jas sprendžiant žingsnis po žingsnio taikant tiesioginio integravimo‐Niumarko metodą. Apskaičiuota abiejų struktūrų viršutinio aukšto absoliučiojo pagreičio ir atramos poslinkio variacija tam, kad būtų nustatyta sujungtos sistemos laikysena ir jos efektyvumas. Nustatyta, kad naudinga jungti gretimus izoliuotus pastatus klampiai tampriais slopintuvais siekiant mažinti didelius atramų poslinkius ir kartu išvengti izoliatorių pažeidimu dėl žemes drebėjimų. Nustatyta, kad jungtis taikant klampiai tamprius slopintuvus yra pati efektyviausia, kai gretimi pastatai yra su izoliuotomis bei fiksuotomis atramomis. Todėl šis būdas naudingas gerinant fiksuotų atramų pastatų seisminį atsparumą, kai jie yra šalia pastatų su izoliuotomis atramomis. Reikšminiai žodžiai: gretimi pastatai, žemės drebėjimas, elastomerinė atrama, seisminis pagrindo izoliavimas, slankioji sistema, renovacija, klampiai tamprus slopintuvas. First Published Online: 14 Oct 2010